Synthesis and gas sorption behaviour of ZIF-90 with large pore volume. (27th October 2017) - Liguori, Paola F.; Russo, Beatrice; Melicchio, Alessandro; Golemme, Giovanni
Abstract : Stoichiometric triethylamine in methanol deprotonates the imidazole and yields 98% sub-micrometric ZIF-90 with no residual solvent in the pores. Abstract : Stoichiometric triethylamine in methanol produces sub-micron ZIF-90 in 98% yield with the largest gas uptakes ever measured. Micropore volume and surface area are compatible with an empty pore network and with crystallographic data, but the occurrence of crystal defects, such as missing ligands or Zn 2+ ions, although improbable, can not be ruled out.